Protein Intake and Mobility Limitation in Community‐Dwelling Older Adults: the Health ABC Study - Houston, Denise K.; Tooze, Janet A.; Garcia, Katelyn; Visser, Marjolein; Rubin, Susan; Harris, Tamara B.; Newman, Anne B.; Kritchevsky, Stephen B. (Journal of the American Geriatrics Society (JAGS), 2017)
Objectives The current Recommended Dietary Allowance (RDA) for protein is based on short‐term nitrogen balance studies in young adults and may underestimate the amount needed to optimally preserve physical function in older adults. We examined the association between protein intake and the onset of mobility limitation over 6 years of follow‐up in older adults in the Health ABC study. Design Prospective cohort study. Setting Memphis, Tennessee and Pittsburgh, Pennsylvania. Participants Community‐dwelling, initially well‐functioning adults aged 70–79 years (n = 1998). Measurements Protein intake (g/kg body weight/d) was calculated using an interviewer‐administered 108‐item food frequency questionnaire at baseline. Mobility limitation was assessed semi‐annually and defined as reporting any difficulty walking one‐quarter of a mile or climbing 10 steps on 2 consecutive 6‐month contacts. The association between protein intake and incident mobility limitation was examined using Cox proportional hazard regression models adjusting for demographics, behavioral characteristics, chronic conditions, total energy intake, and height. Results Mean (SD) protein intake was 0.91 (0.38) g/kg body weight/d, with 43% reporting intakes less than the RDA (0.8 g/kg body weight/d). During 6 years of follow‐up, 705 participants (35.3%) developed mobility limitations. Compared to participants in the upper tertile of protein intake (≥1.0 g/kg body weight/d), participants in the lower two tertiles of protein intake (<0.7 and 0.7 –<1.0 g/kg body weight/d) were at greater risk of developing mobility limitation over 6 years of follow‐up (RR (95% CI): 1.86 (1.41–2.44) and 1.49 (1.20–1.84), respectively). Conclusion Lower protein intake was associated with increased risk of mobility limitation in community‐dwelling, initially well‐functioning older adults. These results suggest that protein intakes of ≥1.0 g/kg body weight/d may be optimal for maintaining physical function in older adults.